Utilização de medicamentos por idosos com diabetes do município de Goiânia, Goiás - Nunes, Marcus Vinicius Oliveira (2013)
Introduction. In Brazil, the percentage of elderly people is increasing considerably over the years. As a consequence, it is observes the increasing of chronical diseases such as diabetes mellitus. It is a disease that requires special attention, because it exposes elderly people to a long care period and to the continued use of medicines, sometimes using multidrugs. Moreover, elderly people are often affected by other comorbidities, by complications of the disease and its treatment. Objective. Analyze the use of medicines by the elderly people with diabetes mellitus in the city of Goiania, Goias, Brazil. Methodology. It is a population-based cross-sectional study carried out with a sample of 173 elderly individuals with diabetes mellitus and medications referred, selected by cluster. Data were collected by household interviews from December 2009 to April 2010 and they were analyzed by the Software Stata 12.0. The identified medicines were classified according to the Anatomical Therapeutic Chemical classification of the World Health Organization. The study was approved by Ethics Committee of the Federal University of Goias . Results. The mean age of old people with diabetes mellitus was 72.5 years and 61.8% were female. The most used medicines were acetylsalicylic acid (20.2%), enalapril (19.1%), dipyrone (13.3%), simvastatin (13.3%), levothyroxine sodium (12.7%), captopril (11.0%), atenolol (11.0%), hydrochlorothiazide (10.4%), losartan (9.8%) and paracetamol (9.8%). Approximately two thirds of the subjects used drugs for treatment of diabetes mellitus, and biguanides, sulfonylureas and insulins that have been most frequently used, showing respective values of 37.0%, 34.7% e 15.0%. Insulin alone was used in 7.5% of the elderly. It was found that 20.2% of the subjects used glibenclamide, an inappropriate medicine for old people. Exclusively oral antidiabetic therapy was observed in 51.5% of the individuals: 68.5% oral monotherapy and 31.5% combined oral therapy. The exclusive use of oral antidiabetic occurred with the utilization of metformin in monotherapy (15.6%), glibenclamide in monotherapy (11.0%) and combined therapy using metformin and glibenclamide (8.1%). The polypharmacy frequency was 38.7%. It was observed that women, unmarried, aged over 75 years and those who were not engaged in physical activity, hypertensive individuals, dyslipidaemic and those who had any hospitalization in the last 12 months had a higher median number of drugs used (p <0.05). However, after multivariate analysis hypertension was he only variable with statistical significance. Older people with diabetes mellitus and hypertension had 3.28 times more likely to use five or more medications than those without hypertension. Conclusion. This study allowed us to identify the profile of utilization of medicines by elderly people with diabetes mellitus as well to verify that metformin, alone or in combination, was the drug most often used for diabetes mellitus and indicated factors that may compromise the safety of antidiabetic pharmacotherapy in this population. Thus, health actions need to be developed, it is essential the work of the pharmacist in the multidisciplinary team to promotion of rational use of medicines and ensuring the safety of the elderly with diabetes mellitus.